Effect of NSAIDS and COX-2 inhibitors on the incidence and severity of asbestos-induced malignant mesothelioma: Evidence from an animal model and a human cohort - Robinson, C.; Alfonso, Helman; Woo, S.; Olsen, N.; Musk, A.; Robinson, B.; Nowak, A.; Lake, R. (Elsevier Ireland Ltd, 2014)
Objectives: Non-steroidal anti-inflammatory drugs (NSAIDs) and COX-2 inhibitors have been associated with lower incidence rates of some cancers. Because asbestos can cause chronic inflammation at the pleural and peritoneal surfaces we hypothesised that NSAID and COX-2 inhibitors would inhibit the development of asbestos-induced mesothelioma. Materials and methods: A murine model of asbestos-induced mesothelioma was used to test this hypothesis by providing the NSAID, aspirin, daily in the feed at 50. mg/kg or 250. mg/kg. In a parallel study, the relationship between the use of NSAID and COX-2 inhibitors and mesothelioma was investigated in a human cohort of 1738 asbestos exposed people living or working in Wittenoom, Western Australia (a crocidolite mine site). Results: Aspirin did not alter the rate of disease development or increase the length of time that mice survived. Aspirin had a small but significant effect on disease latency (the time between asbestos exposure and first evidence of disease; p < 0.05) but disease progression was not affected by the continued presence of the drug. In the Wittenoom cohort, individuals who reported use of NSAIDs, COX-2 inhibitors or both did not have a lower incidence of mesothelioma (HR = 0.85; 95% CI = 0.53-1.37, p= 0.50), (HR = 0.69; 95% CI = 0.21-2.30, p= 0.55) and (HR = 0.43; 95% CI = 0.16-1.13, p= 0.087) respectively. Conclusion: We conclude that NSAIDs and COX-2 inhibitors do not moderate mesothelioma development or progression in a human cohort exposed to asbestos and this result is confirmed in an autochthonous mouse model.